Introducing QWET – A QGIS-plugin for application, evaluation and experimentation with the WET model: Environmental Modelling and Software. (January 2021) - Nielsen, Anders; Schmidt Hu, Fenjuan Rose; Schnedler-Meyer, Nicolas Azaña; Bolding, Karsten; Andersen, Tobias Kuhlmann; Trolle, Dennis
Abstract: We wish to introduce QWET, a new version of the free and open-source QGIS plugin for the aquatic ecosystem model WET. QWET is as a graphical user interface for the application, evaluation and experimentation of WET. Several new features have been incorporated since its predecessor and, here, we demonstrate elements of the new plugin by applying it to Danish Lake Ravn. Among others, we compare model simulations against observations and describe how the scenario platform now supports scheduling of state-variable manipulation, which allows users to explore lake or reservoir restoration interventions such as biomanipulation and oxygenation. With QWET, we seek to aid practitioners who do not possess the sufficient technical expertise to operate a state-of-the art complex model system, such as WET, and thereby hope to facilitate a wider use and adaptation of aquatic ecosystem models.